Effects of a One-Time Application of Controlled-Release Nitrogen Fertilizer on Yield and Nitrogen Accumulation and Utilization of Late Japonica Rice in China - Dong Xu (MDPI AG, 2021)
A mixture of controlled-release nitrogen (N) fertilizers (CRNFs) and conventional urea (CU) as a single application of basal fertilizer could simplify fertilization in rice cultivation from the traditional and more labor-intensive fertilization strategy of multiple applications of nitrogen. However, the reported benefits of this combined approach in increasing rice yield have varied substantially for various reasons, including that various types of rice are characterized by different N requirements to obtain high yield. In this study, two late japonica rice cultivars, Jia58 (J58) and Jia67(J67), were used to determine the best combination of one of two short-acting CRNFs (release periods were 40 and 60 days) and one of three long-acting CRNFs (release periods were 80, 100 and 120 days) to apply with the CU as a one-time application of basal fertilizer. Six combinations of CRNFs were established based on their release periods: A1, 40 + 80 days; A2, 40 + 100 days; A3, 40 + 120 days; B1, 60 + 80 days; B2, 60 + 100 days; and B3, 60 + 120 days. CU applied split at basal, tillering and panicle differentiation stages, respectively as control (CK). The effects of the different treatment combinations of CRNFs on late-rice grain yield, N accumulation and N-use efficiency in a two-year field experiment were determined. Results showed that, the A2 treatment achieved the same yield as that of CK, and yield of the B2 treatment exceeded the yield of CK. Yield of J58 applied with B2 was 7.35% higher in 2018 and 7.40% higher in 2019 than that of the corresponding yield of CK; yield of J67 applied with B2 was 6.05% higher in 2018 and 6.87% higher in 2019 than that of CK. Compared with other CRNF treatments, the release of N from A2 and B2 was most synchronized with nitrogen uptake by the two cultivars, which indicates that fertilizer combination completely met the nitrogen demands during each growth stage of rice. Rice of the A2 and B2 treatments had higher N accumulation, higher aboveground biomass accumulation and LAI (leaf area index) at the heading and maturity stages and higher photosynthetic activity than those of other CRNF treatments. In conclusion, for late japonica rice in China, the application of the A2 and B2 treatments as optimal type of CRNF can achieve labor saving and yield increasing simultaneously in rice production.